Penerapan Teknologi Sentrifugasi dalam Pembuatan Virgin Coconut Oil (VCO) di Desa Bojong, Panjatan, Kulon Progo - Anna Pudianti; Boy Rahardjo Sidharta; Yohana Rustiana; Yitno Purwoko; Kenjikoh Kuputra; Jeremiah Tamba (Jurnal Atma Inovasia, 2026)
Bojong Village has a vast coconut plantation potential, which has been planned for utilization and preservation, particularly as a tourist attraction. Coconuts, with their benefits from the roots to the leaves, have long been protected and developed by the local community, including as a producer of Virgin Coconut Oil (VCO). The Bojong village community has been producing VCO using a traditional "fishing" method, resulting in low-quality and low-quantity results. The purpose of this community service activity in Bojong village is to assist in improving the quality of VCO using centrifugation technology. A high-quality VCO will increase added value, thereby supporting the economy and community welfare. Training on VCO production using centrifugation technology was conducted with varying centrifugation times and coconut ages. The training resulted in a VCO with quality that meets SNI 2022 standards. The best VCO was obtained from mature coconuts, centrifuged for 45 minutes at a rotation speed of 2000 rpm. This assistance has improved the quality of VCO produced by the community, particularly in supporting the development of a coconut-based tourist village in Bojong.